EVALUASI NILAI WAKTU PERJALANAN PENJUAL PASAR TRADISIONAL - Azwanda Azwanda; Meidia Refiyanni; Meri Candra (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
The value of travel time becomes an important part of profits in the assessment of a transportation project in terms of economic considerations. The time value is usually proportional to per-capita income, which is a fixed ratio to the income level. As for the limitations of the problem in this study is only done on a single market contained in the city of Meulaboh Business Market located at Jalan Daud Dariyah II Meulaboh City for the survey by way of filing questionnaires to kiosk owners and employees stalls Market Business as respondents , As well as compiling survey results into planned formats. The questionnaire data is inputted and then recapitulated to be analyzed by Kolmogorov-Sminnov Normality test method to ensure valid / normal data, and analysis ofspearman's rho and kendall's tau test methods in SPSS (Statistical Product and Service Solution) software. Based on the analysis of time value of go-and-go time of the seller, for the kiosk owner the time value goes 567,41 Rp / minute and the return time value is 108,18 Rp / minute. Sedangka for employees kiosk 691,68 Rp / minute (go) and 108,00 Rp / minute (go home). Furthermore, the results of the normality test stages by kolmogorov-smirnov with SPSS (Statistical Product andService Solution) method show that the output of the travel costs of owners and employees of kiosks (go-home), and the value of time owners and employees kiosk (go-go ) Value significance correction (Sig) <0.05, means that data is not normally distributed. Implementation on the data normality test (kolmogorov-smirnov) if the significance is below 0.05, means that the data has a significant difference with the normal raw data. Furthermore, non-parametric statistic is used with spearman's rho and kendall's tau, to know the relationship between travel cost and travel time value. The result of spearman's rho correlation shows positive number (+) on correlation coefficien, as well as correlation coefficien's correlation or tau indicates positive number (+) on correlation coefficien, meaning the greater the travel cost the greater the travel time. Keywords: Seller, Traditional Market, Travel Time Abstract